Downregulation of ADAM10 Expression Inhibits Metastasis and Invasiveness of Human Hepatocellular Carcinoma HepG2 Cells. (14th July 2013) - Yue, Yuan; Shao, Yuan; Luo, Qing; Shi, Lei; Wang, Zuoren
Abstract : Objective . This study aims to investigate the effects of ADAM10 expression on metastasis and invasiveness of human hepatocellular carcinoma HepG2 cells. Methods . The HepG2 cells were transfected with medium only, the empty vector, the control siRNA, or siRNA against ADAM10, respectively. Cell migration assay and Transwell invasiveness assay were performed to detect the effects of ADAM10 knockdown on migration and invasiveness of HepG2 cells. Western blotting and real-time RT PCR were performed to investigate the effects of knock-down of ADAM10 on protein and mRNA levels of E-cadherin gene. Results . Cell migration and invasiveness of HepG2 cells transfected with ADAM10 siRNA were significantly decreased, when compared with the cells transfected with the control siRNA, suggesting that the downregulation of ADAM10 expression inhibits cell migration and invasiveness. The Western blotting results suggest that the down-regulation of ADAM10 expression increases E-cadherin protein levels. The real-time RT-PCR results indicated that the mRNA level of E-cadherin is not detectably affected by the knock-down of ADAM10 gene. Conclusions . Expression of ADAM10 may be related to cell migration and invasiveness of human hepatocellular carcinoma HepG2 cells via a mechanism related to E-cadherin.